PENDIDIKAN KARAKTER DALAM PERSPEKTIF AL-QUR’AN - Lutfiatul Jannah (LPPM STAI Muhammadiyah Probolinggo, 2020)
The rise of moral degradation that occurred in Indonesia until now is still a fetter for the community, especially among young people who are the nation's successors. Various kinds of criminal acts experienced a rapid increase. Promiscuity among adolescents, even at the elementary school level that is still underage, drug abuse and illegal drugs, bullying in schools, corruption, collusion and nepotism are increasingly rampant, domestic violence (domestic violence), human trafficking online , theft and even kidnapping and so on. One of the main factors in the occurrence of various kinds of criminal acts is moral degradation caused by the negative influence of Western culture and mindset that is too vulgar and not in accordance with prevailing norms. Indonesia, the majority of the population embraces Islam, the author will answer two problems, the first is to understand character education, and second is how the concept of character education in the perspective of the Qur'an.